PERSIAPAN RUANG MUAT CURAH DI MV. NOAH ASYERA - Rahman, Aulia; Welem Ada; Firnayanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The current work aims to explore the elements leading to delays in bulk cargo hold preparation and to identify the efforts that can be made to overcome these obstacles on MV. Noah Asyera. The research method used is descriptive qualitative. Data were obtained through direct observation, in-depth interviews, and documentation during sea practice. The analysis method used is the Miles and Huberman interactive model. The results indicate that cargo hold preparation was hindered by three main factors: human factors (weak supervision by watch officers, lack of crew coordination, and limited technical skills), equipment factors (damaged nozzles, brooms, shovels, and suboptimal bilge pumps), and material factors (the sticky and abrasive nature of Copper concentrate residue and residual seawater in the bilge). The impacts of these obstacles include cargo holds being declared unfit during surveyor inspection, loading process delays, increased operational costs, and disrupted voyage schedules. The efforts undertaken to overcome these obstacles include enhanced supervision, conducting toolbox meetings, using submersible pumps as alternatives, regular equipment maintenance, implementing efficient cleaning methods, and crew competency training. Consistent implementation of Standard Operational Procedures (SOP) prevents loading delays and maintains compliance with the International Maritime Solid Bulk Cargoes (IMSBC) Code standards.